2013
DOI: 10.1088/1367-2630/15/7/075006
|View full text |Cite
|
Sign up to set email alerts
|

Collective cell streams in epithelial monolayers depend on cell adhesion

Abstract: We report a spontaneously emerging, randomly oriented, collective streaming behavior within a monolayer culture of a human keratinocyte cell line, and explore the effect of modulating cell adhesions by perturbing the function of calcium-dependent cell adhesion molecules. We demonstrate that decreasing cell adhesion induces narrower and more anisotropic cell streams, reminiscent of decreasing the Taylor scale of turbulent liquids. To explain our empirical findings, we propose a cell-based model that represents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 57 publications
0
49
0
Order By: Relevance
“…Accordingly, the extension of the CPM allows to leave considering cells as passive objects, giving them the possibility to actively explore the environment beyond the local fluctuations of their cell membranes, both in the presence or absence of external signals. This extension has been used to model the D. discoideum morphogenesis [19][20][21], to investigate collective cell migration (or motion) in Szabó et al [36], Kabla [37], Czirók et al [55], and Czirók et al [56], and more recently to study the chemotactic response of cells [45]. In this paper, following the line of pioneering works that use the CPM to study persistent cell motion in the absence of external cues [33,36], we take advantage of a directional propensity vector linked to a first order autoregressive process that governs the dynamics of cell movement direction.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the extension of the CPM allows to leave considering cells as passive objects, giving them the possibility to actively explore the environment beyond the local fluctuations of their cell membranes, both in the presence or absence of external signals. This extension has been used to model the D. discoideum morphogenesis [19][20][21], to investigate collective cell migration (or motion) in Szabó et al [36], Kabla [37], Czirók et al [55], and Czirók et al [56], and more recently to study the chemotactic response of cells [45]. In this paper, following the line of pioneering works that use the CPM to study persistent cell motion in the absence of external cues [33,36], we take advantage of a directional propensity vector linked to a first order autoregressive process that governs the dynamics of cell movement direction.…”
Section: Discussionmentioning
confidence: 99%
“…To study collective migration of cell sheets CPMs often use a velocity alignment model which takes memory effects and polarity alignment of interacting cells into account. This variant has been successfully used to study cell-ECM invasion, 95 T-cell migration into lymph nodes, 96 tumor growth and invasion, 117 and the transition to collective motion 97,98 matching experimental observations for the formation of swirls on circular MP 99 . Velocity alignment is a coarse grained mechanism to describe cell motility and CPMs allow for a more detailed description of the motility mechanism.…”
Section: Dynamic Cell Shape Modelsmentioning
confidence: 93%
“…The model has similar velocities for cell motion either in isotropic or anisotropic matrices but with an increase in persistence for the latter. It is worth noting that the model proposed in [27] considered only isolated cells interacting with the environment, whereas the model proposed in [30] included a cellular Potts formalism describing collective cell streams in epithelial monolayers [47]. In this case, it was concluded that intercellular adhesion modulated the extent of cell groups undergoing local collective movements in the monolayer.…”
Section: Cell-based Models Describing Experimental Datamentioning
confidence: 99%
“…Cell motility was further modulated by a number of mechanisms in which relevant variables from both the ECM and the cell itself were included [29]. A cell-based model with a cellular Potts formalism describing spontaneously emerging, randomly oriented collective cell streams within a human keratinocyte culture monolayer has also been reported [30]. In this model, by changing the relevance of mechanical links between cells, the experimental findings that cell streams become narrower with the decrease in cell-cell adhesion have been explained.…”
Section: Introductionmentioning
confidence: 99%